Implantable Cardioverter-Defibrillator Shock Delivered During Electroconvulsive Therapy Despite Magnet Application: A Case Report. Issue 11 (September 2020) - Streckenbach, Scott C.; Benedetto, William J.; Fitzsimons, Michael G.
Abstract : Electroconvulsive therapy (ECT) in a patient with an implantable cardioverter-defibrillator (ICD) presents challenges to anesthesiologists. We encountered a patient who received an inappropriate shock during ECT despite magnet application. The phenomenon provides insight into how ICDs work—how they can inappropriately detect ECT stimulation and how they deliver antitachycardia therapy. We illuminate issues related to using magnets, discuss risks associated with inappropriate ICD therapy, and provide guidance for ICD management during ECT.